Nilai Pelanggan di Cek Toko Sebelah App - Sri Lestari (Penerbit Goodwood, 2022)
Purpose: Provides an overview of the usability of the browser extension Cek Toko Sebelah App. Methodology: Descriptive methods are used to describe or analyze but cannot draw broad conclusions. Results: Cek Toko Sebelah App has an advantage over other price comparators because it is a web browser extension. It allows users to directly compare prices on their favorite shopping sites without searching on other sites (third parties). Limitations: This article only focuses on Cek Toko Sebelah App with data obtained from digital traces. Contribution: Cek Toko Sebelah App claimed as